Impact of operating cycle type on alginate-like exopolysaccharide (ale) and tryptophan production in aerobic granular sludge systems - Barros, Amanda Nascimento de (2024)
With the wastewater industry’s continuous development, wastewater treatment plants more frequently integrate pollutant removal and resource recovery. Aerobic granular sludge (AGS) is recognized as an efficient emerging treatment technology whose extracellular polymeric substances (EPS) account for a considerable proportion of the biomass dry mass. Thus, the main objective of the study was to evaluate the cycle type impact (distribution time between anaerobic and aerobic phases) on the EPS and bioresources (alginate-like exopolysaccharide-ALE and tryptophan) productions in AGS systems. The main specific objectives are: to conduct a literature review related to bioresources production and recovery in AGS systems; to develop and validate an analytical method for determining tryptophan in aerobic granular sludge (AGS); to evaluate the selectivity, linearity, precision, accuracy, detection limit, and quantification limit parameters of the tryptophan quantification method; to evaluate in continuous-flow operation the cycle type impact on carbon and nutrients removals and bioresources productions in AGS systems; to evaluate the application of the validated method in the quantification of tryptophan in continuous-flow AGS reactors. Two sequencing batch reactors (SBRs) were operated for continuous flow experiments, fed with synthetic wastewater, and used a 6-hour total cycle, varying the anaerobic phase (100, 70, 35, and 0 minutes). The carbon sources selected were acetic acid for R1 and propionic acid for R2. The method for the determination of tryptophan was validated for a linear range of 1 ppm to 50 ppm, with a detection limit of 1.1 ppm and a quantification limit of 3.4 ppm. COD, N, and P removals were similar, but R2 exhibited a higher nitrate accumulation. Statistical analysis revealed significant differences in the EPS content during the phases of both systems, with p < 0.05. The cycle configuration, specifically the distribution of anaerobic and aerobic times in AGS systems, affects the production of ALE, EPS, and TRP. While the extended anaerobic period favored ALE production in the R1 system, possibly due to a reduced famine period, the high SRT in R2 exerted a more substantial influence, maintaining ALE levels despite cycle changes. The size of the granules, rather than AGS concentration, plays a role in the EPS and ALE productions. Regarding tryptophan production, reducing the anaerobic period can increase its yield, offering opportunities for future optimization. However, the complexity and variability of these bioresources highlight the need for more comprehensive investigations to unravel the nuances of their production in real-scale treatment systems. Thus, the operational cycle has a different effect on the bioresources productions (ALE and tryptophan).